Reading/Writing Canada: a Facebook Wall about Canadian Literature - Graciela Martínez-Zalce (Norteamérica)
The CBC operates on a mandate that defines it as a company of content whose vision is to connect Canadians through attractive Canadian content and whose values include serving the Canadian public. This article responds to the questions of how the CBC uses social media to disseminate national literatures, taking a Facebook wall Canada Reads, as a case study, based on the small stories method (Georgakoupoulou) to analyze narrative activities that are important for recognizing the identity-forging work of their narrator as well as the social fabric of practices that people become involved in, with the objective of discovering if it has created a virtual community of practice (as conceived by Robert V. Kozinets) and if it has achieved, at the same time, the ultimate goal of discussing contemporary Canadian identities and if it has fulfilled its aim to disseminated contemporary regional and national quality content.